Shakespeare and the Theater of Religious Conviction in Early Modern England - Lim, Walter S H. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
In this wide-ranging and informative study, Walter Lim throws new light on the meaning of religion in Shakespeare and post-Reformation culture. Buttressing close analysis with comparative study, Lim shows not only how Shakespeare rethinks religious concepts such as sin, salvation, and belief, but also how his plays reveal the mixture of sacred and secular perspectives that shaped early modern cultural practices, from government, commerce, and law to sexuality, radical politics, and overseas travel. -Kenneth Graham, Department of English, University of Waterloo "Walter Lim's book is an accessible and wide-ranging study of five Shakespearean plays in the context of early modern spirituality and religious controversy. His inventive placing of the plays in dialogue with other seventeenth-century texts such as Aemilia Lanyer's poetry and the Royalist volume Eikon Basilike makes this a particularly welcome contribution to the expanding critical field of Shakespeare and religion." -Helen Wilcox, Professor Emerita of English Literature, Bangor University. This book analyzes Shakespeare's use of biblical allusions and evocation of doctrinal topics in Hamlet, Measure for Measure, The Winter's Tale, Richard II, and The Merchant of Venice. It identifies references to theological and doctrinal commonplaces such as sin, grace, confession, damnation, and the Fall in these plays, affirming that Shakespeare's literary imagination is very much influenced by his familiarity with the Bible and also with matters of church doctrine. This theological and doctrinal subject matter also derives its significance from genres as diverse as travel narratives, sermons, political treatises, and royal proclamations. This study looks at how Shakespeare's deployment of religious topics interacts with ideas circulating via other cultural texts and genres in society. It also analyzes how religion enables Shakespeare's engagement with cultural debates and political developments in England: absolutism and law; radical political theory; morality and law; and conceptions of nationhood. Walter S H Lim is an Associate Professor of English Literature at the National University of Singapore. He is the author of Narratives of Diaspora: Representations of Asia in Chinese American Literature (2013); John Milton, Radical Politics, and Biblical Republicanism (2006); and The Arts of Empire: The Poetics of Colonialism from Ralegh to Milton (1998). He also co-edited the collection The English Renaissance, Orientalism, and the Idea of Asia (2010).
1. Shakespeare and the Theater of Religious Conviction in Early Modern England -- 2. Dying Unshriven and the Afterlife in Hamlet -- 3. Temptation, Fornication, and the Fall in Measure for Measure -- 4. Biblical Faith and Radical Politics in The Winter's Tale -- 5. Grief, Gardens, and the Staging of Tragedy in Richard II -- 6. Surety, Usury, Hazard, and Spiritual Commercialism in The Merchant of Venice.
Keywords: European literature -- Renaissance, 1450-1600.; Religion; Literature -- History and criticism; Theater -- History; Early Modern and Renaissance Literature; Religion; Literary History; Theatre History